The open-endedness of macroprudential policy. Endogenous risks as an obstacle to countercyclical financial regulation. (March 2020) - Stellinga, Bart
Abstract: After the global financial crisis of 2007–9, policymakers hailed macroprudential policy as the solution to financial markets' boom-bust patterns. Financial regulations would have to operate countercyclically, increasing in stringency during a boom while becoming lenient in a bust. Simultaneously, the procyclical effects of pre-crisis rules would have to be eliminated. Actual reforms, however, do not live up to these high hopes. In addition to the countercyclical policy framework's limited scope and ambition, its open-endedness is particularly striking. As policymakers have not specified when supervisors should (de)activate what instruments and how firms should measure risk, there is an inbuilt indeterminacy at macroprudential policy's core. I argue that obstacles inherent to the nature of systemic risk are key to understanding this policy outcome. As the financial system is reflexive, adaptive, and complex, there are hard limits to supervisors' ability to "read" the financial cycle. Furthermore, as macroprudential policy itself becomes "part of financial markets, " countercyclical interventions may have systemically significant unintended consequences. This article empirically shows how policymakers at the global and EU level, confronted with these measurement and mitigation problems, ultimately opted for a limited and open-ended policy framework.